Hot-Air Spinning Technology Enables the High-Efficiency Production of Nanofiber - Guo-Dong Zhang; Yuan Gao; Pi-Hang Yu; Chao Zhang; Chuan-Hui Guo; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Nanomaterials)
Water is the most environmentally friendly solvent; however, conventional solution spinning using water as a solvent is challenging due to its low evaporation rate. We developed a double-pronged solution blow spinning (DP-SBS) system. This spinning technique significantly enhances solvent evaporation, and the designed structure (double-pronged) avoids the common problem of needle clogging caused by heating. DP-SBS enables high-yield production of water-soluble polymer nanofibers, with a production rate of up to 5.94 g/h, which far exceeds what can be achieved with traditional electrospinning or solution blow spinning. This method is also highly efficient for producing non-water-soluble polymer nanofibers, achieving a production rate of up to 7.91 g/h, the highest reported value to date. Additionally, this approach can be used to produce not only common two-dimensional fiber membranes but also fiber sponges in a single step using the double-pronged airflow system. For the first time, chitosan nanofiber sponges were successfully produced and demonstrated to have excellent hemostatic properties in medical hemostasis. This method can also be extended to the production of other 3D nanomaterials, such as mullite nanofiber sponges, which exhibit outstanding thermal insulation performance at high temperatures.